Studi Perbandingan Hasil Teknik Freehand Nail Art dengan Teknik Stamping Nail Art - Rahmma Eka Adi Susanti; Rahmiati Rahmiati (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to determine the differences in nail art results using the freehand technique and the stamping technique on artificial nails, reviewed from four aspects, namely neatness, color evenness, preference, and aesthetics. The research method used is a quantitative experiment involving 80 artificial nails, 40 artificial nails with the freehand technique and 40 artificial nails with the stamping technique. The assessment was carried out by a panel consisting of lecturers, beauty industry practitioners, and students of Makeup and Beauty at Padang State University. Data were obtained through observation and documentation, then analyzed using the Mann-Whitney U test. The results showed that there were significant differences between the two techniques. The stamping technique was superior in terms of neatness and color evenness, while the freehand technique was superior in terms of aesthetics and preference. Based on the Mann-Whitney U test, a significant value of 0.030 <0.050 was obtained, which means there is a significant difference between the freehand technique and the stamping technique in terms of neatness. A significant value of 0.734>0.05 indicates that there is no significant difference between the freehand technique and the stamping technique in terms of color evenness. The significant value is 0.003 <0.05, which means there is a significant difference in the beauty aspect of the freehand technique and the stamping technique. In the aspect of liking the significant value is 0.163>0.05, which means there is no significant difference between the freehand technique and the stamping technique. These findings contribute to the development of nail art learning and become a practical reference in choosing techniques according to aesthetic and efficiency needs.